Biomedical applications of acridines : derivatives, syntheses, properties and biological activities with a focus on neurodegenerative diseases /: derivatives, syntheses, properties and biological activities with a focus on neurodegenerative diseases. (2017) - (Organic chemist), Ježek, Jan; Hlavacek, Jan, 1969-; Šebestík, Jaroslav
No abstract available